2018
DOI: 10.1080/00325481.2018.1515563
|View full text |Cite
|
Sign up to set email alerts
|

Emotional intelligence and leadership traits among family physicians

Abstract: Emotional intelligence and leadership traits play crucial roles in increasing physicians' personal and professional development. This may also increase physicians' caregiving competencies and thus the quality of health services, as well as potentially decreasing physicians' burnout and health-related costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 15 publications
1
12
0
1
Order By: Relevance
“…This agrees with the results of Dolev, et al, [23]. On the other hand, many other studies suggested that EI improves with increasing age [24,25]. This difference may be due to differences in the target populations.…”
Section: Discussionsupporting
confidence: 92%
“…This agrees with the results of Dolev, et al, [23]. On the other hand, many other studies suggested that EI improves with increasing age [24,25]. This difference may be due to differences in the target populations.…”
Section: Discussionsupporting
confidence: 92%
“…12 Studies performed in the medical field reported similar conclusions; in a large Turkish survey focused on family physicians, emotional intelligence scores varied significantly according to sex, geographic region, and experience, and the emotional intelligence scores correlated significantly with leadership traits. 13…”
Section: Introductionmentioning
confidence: 99%
“…This was a descriptive population-based study conducted from September 2013 to December 2014. The total population comprised 20,185 family physicians working at family healthcare centers across the seven regions of Turkey [27]. Women scored higher than did men for well-being, emotionality, and global TEI, which reflect similar GME outcomes.…”
Section: Emotional Intelligence and Leadership Traits Among Family Physiciansmentioning
confidence: 94%